Haemodynamic outcomes during piston-based mechanical CPR with or without active decompression in a porcine model of cardiac arrest - Mikkel T. Steinberg; Jan-Aage Olsen; Morten Eriksen; Andres Neset; Per Andreas Norseng; Jo Kramer-Johansen; Bjarne Madsen Hardig; Lars Wik (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2018)
Abstract Background Experimental active compression-decompression (ACD) CPR is associated with increased haemodynamic outcomes compared to standard mechanical chest compressions. Since no clinically available mechanical chest compression device is capable of ACD-CPR, we modified the LUCAS 2 (Physio-Control, Lund, Sweden) to deliver ACD-CPR, hypothesising it would improve haemodynamic outcomes compared with standard LUCAS CPR on pigs with cardiac arrest. Methods The modified LUCAS delivering 5 cm compressions with or without 2 cm active decompression above anatomical chest level was studied in a randomized crossover design on 19 Norwegian domestic pigs. VF was electrically induced and untreated for 2 min. Each pig received ACD-CPR and standard mechanical CPR in three 180-s. phases. We measured aortic, right atrial, coronary perfusion, intracranial and oesophageal pressure, cerebral and carotid blood flow and cardiac output. Two-sided paired samples t-test was used for continuous parametric data and Wilcoxon test for non-parametric data. P < 0.05 was considered significant. Results Due to injuries/device failure, the experimental protocol was completed in nine of 19 pigs. Cardiac output (l/min, median, (25, 75-percentiles): 1.5 (1.1, 1.7) vs. 1.1 (0.8, 1.5), p < 0.01), cerebral blood flow (AU, 297 vs. 253, mean difference: 44, 95% CI; 14–74, p = 0.01), and carotid blood flow (l/min, median, (25, 75-percentiles): 97 (70, 106) vs. 83 (57, 94), p < 0.01) were higher during ACD-CPR compared to standard mechanical CPR. Coronary perfusion pressure (CPP) trended towards higher in end decompression phase. Conclusion Cardiac output and brain blood flow improved with mechanical ACD-CPR and CPP trended towards higher during end-diastole compared to standard LUCAS CPR.